Astroglial Glutamate Signaling and Uptake in the Hippocampus - Rose, Christine R.; Felix, Lisa; Zeug, Andre; Dietrich, Dirk; Reiner, Andreas; Henneberger, Christian (Frontiers in Molecular Neuroscience, 2018)
Astrocytes have long been regarded as essentially unexcitable cells that do not contribute to active signaling and information processing in the brain. Contrary to this classical view, it is now firmly established that astrocytes can specifically respond to glutamate released from neurons. Astrocyte glutamate signaling is initiated upon binding of glutamate to ionotropic and/or metabotropic receptors, which can result in calcium signaling, a major form of glial excitability. Release of so-called gliotransmitters like glutamate, ATP and D-serine from astrocytes in response to activation of glutamate receptors has been demonstrated to modulate various aspects of neuronal function in the hippocampus. In addition to receptors, glutamate binds to high-affinity, sodium-dependent transporters, which results in rapid buffering of synaptically-released glutamate, followed by its removal from the synaptic cleft through uptake into astrocytes. The degree to which astrocytes modulate and control extracellular glutamate levels through glutamate transporters depends on their expression levels and on the ionic driving forces that decrease with ongoing activity. Another major determinant of astrocytic control of glutamate levels could be the precise morphological arrangement of fine perisynaptic processes close to synapses, defining the diffusional distance for glutamate, and the spatial proximity of transporters in relation to the synaptic cleft. In this review, we will present an overview of the mechanisms and physiological role of glutamate-induced ion signaling in astrocytes in the hippocampus as mediated by receptors and transporters. Moreover, we will discuss the relevance of astroglial glutamate uptake for extracellular glutamate homeostasis, focusing on how activity-induced dynamic changes of perisynaptic processes could shape synaptic transmission at glutamatergic synapses.